2020
DOI: 10.3390/cancers12051279
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EpCAM by a Bispecific Trifunctional Antibody Exerts Profound Cytotoxic Efficacy in Germ Cell Tumor Cell Lines

Abstract: Outcome in high-risk patients with refractory or relapsed germ cell tumours (GCT) remains poor. Novel strategies enhancing therapeutic efficacy whilst limiting therapeutic burden are warranted, yet immunotherapy approaches geared towards activating endogenous antitumor responses have not been successful thus far. Redirection of cytotoxic effector cells by bispecific antibodies represents a promising approach in this setting. We demonstrate that the Epithelial Cell Adhesion Molecule (EpCAM) is broadly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…This event promotes the formation of cytotoxic synapse and T-cell-mediated cytotoxicity. Furthermore, catumaxomab recruits natural killer (NK) cells and macrophages through the Fc domain and enhances antibody-dependent cellular cytotoxicity (Adcc) (16,17). catumaxomab has demonstrated promising outcomes in several clinical trials (18)(19)(20), and has been approved by the European Union for the treatment of patients with malignant ascites (21).…”
Section: Antitumor Activities Of a Defucosylated Anti-epcam Monoclona...mentioning
confidence: 99%
“…This event promotes the formation of cytotoxic synapse and T-cell-mediated cytotoxicity. Furthermore, catumaxomab recruits natural killer (NK) cells and macrophages through the Fc domain and enhances antibody-dependent cellular cytotoxicity (Adcc) (16,17). catumaxomab has demonstrated promising outcomes in several clinical trials (18)(19)(20), and has been approved by the European Union for the treatment of patients with malignant ascites (21).…”
Section: Antitumor Activities Of a Defucosylated Anti-epcam Monoclona...mentioning
confidence: 99%
“…Catumaxomab binds to EpCAM-overexpressed tumors and recruits T cells to tumor cells, which promote cytotoxic synapse formation and tumor cell lysis. Furthermore, through the Fc domain, Catumaxomab also recruits natural killer cells and macrophages and enhances antibody-dependent cellular cytotoxicity (ADCC) [ 8 , 9 ]. Several clinical trials have demonstrated promising outcomes [ 10 , 11 , 12 ], and Catumaxomab has been approved by the European Union for the treatment of patients with malignant ascites in EpCAM-positive carcinomas [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Catumaxomab recognizes EpCAM on tumors, recruits T cells through the anti-CD3 arm, and recruits natural killer (NK) cells and macrophages through the Fc domain. These events enhanced ADCC activity [ 22 ]. Catumaxomab exhibited promising outcomes in several clinical trials [ 23 , 24 , 25 ], and was approved by the European Union for the treatment of patients with malignant ascites in 2009 [ 23 ].…”
Section: Introductionmentioning
confidence: 99%